A multifunctional enzyme portfolio for α-chaconine and α-solanine degradation in the Phthorimaea operculella gut bacterium Glutamicibacter halophytocola S2 encoded in a trisaccharide utilization locus - Wang, Wenqian; Du, Guangzu; Yang, Guangyuan; Zhang, Ke; Chen, Bin; Xiao, Guanli (Frontiers in Microbiology, 2022)
Steroidal glycoalkaloids (SGAs) are secondary metabolites commonly found in members of the family Solanaceae, including potatoes, and are toxic to pests and humans. The predominant SGAs in potato are α-chaconine and α-solanine. We previously reported that Glutamicibacter halophytocola S2, a gut bacterium of the pest Phthorimaea operculella (potato tuber moth), can degrade α-chaconine and α-solanine in potatoes, which can improve the fitness of P. operculella to feed on potatoes with a high content of toxic SGAs. G. halophytocola S2 harbored a gene cluster containing three deglycosylase genes—GE000599, GE000600, and GE000601—that were predicted encode α-rhamnosidase (RhaA), β-glucosidase (GluA), and β-galactosidase (GalA). However, there is limited information is available on the enzyme activities of the three enzymes expressed by this gene cluster and how they degrade the major toxic α-chaconine and α-solanine. In the current study, each enzyme of this gene cluster was produced by a prokaryotic expression approach and the activity of the recombinant enzymes for their target substrate and α-chaconine and α-solanine were evaluated by EPOCH microplate spectrophotometer and liquid chromatography mass spectrometry (LC-MS). The three enzymes had multifunctional activities, with RhaA and GluA could hydrolyze α-rhamnose, β-glucose, and β-galactose, while GalA can hydrolyze β-glucose and β-galactose. The degradation of α-chaconine and α-solanine was consistent with the results of the enzyme activity assays. The final product solanidine could be generated by adding RhaA or GluA alone. In conclusion, this study characterized the multifunctional activity and specific degradation pathway of these three enzymes in G. halophytocola S2. The three multifunctional enzymes have high glycosidic hydrolysis activity and clear gene sequence information, which help facilitates understanding the detoxification mechanism of insect gut microbes. The enzymes have a broad application potential and may be valuable in the removal of toxic SGAs from for potato food consumption.